PENGARUH AKUPRESUR TERHADAP PENINGKATAN KEKUATAN OTOT DAN ACTIVITIES OF DAILY LIVING (ADL) PADA PASIEN STROKE NON HEMORAGIK DI UNIT STROKE RSUD A. WAHAB SJAHRANIE SAMARINDA - Theresia Tutik Ismiati (Unit Penelitian dan Pengabdian Kepada Masyarakat, STIKES Dirgahayu Samarinda, 2019)
Stroke is a disease caused by the interruption of blood supply to the brain. WHO (World Health Organization) stated 15 million people world wide suffer a stroke each year. As many as 5 million people are death sand 5 million people have permanent disability. Stroke Foundation of Indonesia (Yastroki) noted that Indonesia ranks first in Asia with the majority of stroke patients and become leading causes of death in Indonesia. Stroke affects extremity dysfunction such decreased muscle strength which will contribute to the decline ability of Activities of daily living (ADL). There are several the rapies that have been done to over come muscle weakness and limitations of the ADL such as range of movement exercises, positioning, and acupressure is one form of therapy that can be done to restore extremity function. This study aims to determine the effect of acupressure intervention on limb muscle strength and Activities Of Daily Living (ADL) In Stroke Patients. Quantitative Study of quasi-experiment pre-post test design involved 113 respondents into two groups: the intervention group with 88 respondents and the control group with 25 respondents.The result showed male respondents (51.3%), aged 45-59 years (58.4%), and the first attack (85%). After the intervention of 7 day sine ach ofthe respondents, found significant differences increase muscle strength and ADL before the after intervention: right limbmuscle strength(p =0.000); left limbstrength (p =0.000); and ADL (p =0.000). Respondent characteristics that influence muscle strength and ADL were age and frequency of stroke (P <0.05), where as no influence of gender (p> 0.05). The conclusions of this study that acupressureis an effective therapy on increase muscle strength and ADL of stroke patients. This research recommended acupressure as a complementary therapy to improve muscle strength andADLof stroke patients.